Desafios do mercado para os produtos de origem animal da agricultura familiar (Revista Brasileira Multidisciplinar, 2022)
The family farming has a great importance in the food production in Brazil, hoewer this sector is most often not highlighted and faces several difficulties, including the commercialization of products, mainly those of animal origin. Thus, a literature review was carried out to collect informations about the characteristics of livestock in family farming the ways of transporting animal products and the alternatives for valuing these products. The system of animal handling in the family agricultural shows its own characteristcs which depend of cultural and environment issues from each community, therefore must be considered when proposing ways to market these products.Family agricultural shows difficulties of market the animal product in the formal market mainly  due to the difficulty in meeting the legal requirements of inspection services moreover the public policies has been developing are not adjusted of the reality of the rural families. Thereby gets important to encourage the reformulation of public policies like “Selo Arte” and “geographic location” with adequacies that support the family farms and consolidate the Agroecology in Search of major appreciation by the animal products from the Family farms.